Probiotic bacteria of wild boar origin intended for piglets - An in vitro study - Kostovova, Iveta; Kavanova, Katerina; Moravkova, Monika; Gebauer, Jan; Leva, Lenka; Vicenova, Monika; Babak, Vladimir; Faldyna, Martin; Crhanova, Magdalena (Veterinarni medicina, 2024)
Using probiotics represents a potential solution to post-weaning diarrheal diseases in piglets on commercial farms. The gastrointestinal tract of wild boars serves as a promising reservoir of novel lactic acid bacteria with suitable probiotic characteristics. In this study, we isolated eight bacterial strains from the intestinal content of wild boars identified as representatives of the species Bifidobacterium apri, Lactobacillus amylovorus, and Ligilactobacillus salivarius. These isolates underwent in vitro analysis and characterisation to assess their biological safety and probiotic properties. Analysis of their full genome sequences revealed the absence of horizontally transferrable genes for antibiotic resistance. However, seven out of eight isolates harboured genes encoding various types of bacteriocins in their genomes, and bacteriocin production was further confirmed by mass spectrometry analysis. Most of the tested strains demonstrated the ability to inhibit the growth of selected pathogenic bacteria, produce exopolysaccharides, and stimulate the expression of interleukin-10 in porcine macrophages. These characteristics deem the isolates characterised in this study as potential candidates for use as probiotics for piglets during the post-weaning period.
Keywords: exopolysaccharides; antimicrobial activity; antibiotic susceptibility; interleukin-10; bacteriocins